Kubernetes best practices : blueprints for building successful applications on Kubernetes - Burns, Brendan, 1976-; Villalba, Eddie; Strebel, Dave; Evenson, Lachlan (O'Reilly Media, Inc., 2023)
In this practical guide, four Kubernetes professionals with deep experience in distributed systems, enterprise application development, and open source will guide you through the process of building applications with this container orchestration system. They distill decades of experience from companies that are successfully running Kubernetes in production and provide concrete code examples to back the methods presented in this book. Revised to cover all the latest Kubernetes features, new tooling, and deprecations, this book is ideal for those who are familiar with basic Kubernetes concepts but want to get up to speed on the latest best practices. You'll learn exactly what you need to know to build your best app with Kubernetes the first time.